Evaluating the Effect of Accelerated Aging at Different Temperature and Time Points on Beef Quality and Enzyme Activity of Lower Quality Beef Cuts - H. Jeneske; C. K. Chun; S. Hene; L. A. Koulicoff; H. Aufdemberge; J. L. Vipham; T. G. O'Quinn; M. D. Chao (Kansas Agricultural Experiment Station Research Reports, 2023)
Objective:This study aimed to explore the effects of four accelerated aging (AA) methods at different temperature and time points on meat quality and enzymatic activity of two lower quality beef cuts. Study Description:Shoulder clod and top round were collected from 10 U.S. Department of Agriculture choice beef carcasses, fabricated into steaks, and assigned to one of six treatments: 3 days postmortem (control), cooler aged for 21 days, AA 120°F for 2 h, AA 120°F for 3 h, AA 130°F for 2 h, and AA 130°F for 3 h. Yield was calculated based on loss during AA and cooking loss, and purge was collected for collagen analysis. Warner-Bratzler shear force (WBSF) was determined, and purge for microbial analysis was collected from primal bags as well as the package after AA treatment. Steak surfaces were swabbed on the anterior side prior to AA treatment, then swabbed on the posterior side after treatment. Aerobic plate counts (APC) were performed on purge and swab samples. Cathepsin activity was determined through zymography. Soluble collagen content and total collagen in the purge were determined through hydroxyproline content. Results:All AA treatments decreased APC on the steak surfaces (P<0.01) and in the purge (P<0.05). The 130°F samples had a lower yield after AA than the 120°F groups (P<0.05). The cooler aged samples had a lower cook yield than all of the AA samples (P<0.01), and shoulder clod samples displayed higher cooking yield than the top round (P<0.01). The WBSF results showed that AA 120°F for 3 h samples and both AA 130°F samples displayed similar tenderness to the samples that were cooler aged for 21 days (P<0.01). All the AA treatments had higher collagen in the purge than the control or cooler aged samples (P<0.01). There was heightened cathepsin enzymatic activity during all treatments when compared to the control samples, and the AA at 120°F for 3 h treatment displayed the highest activity compared to other AA treatments (P<0.01). The Bottom Line:Accelerated aging has shown to be a promising technique to increase value in lower priced beef cuts through increasing enzymatic activity and tenderness without accelerating microorganism growth.
Keywords: accelerated aging; cathepsin; collagen